2023
DOI: 10.1186/s40001-023-01086-7
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on the efficacy of monocyte distribution width (MDW) as a screening test for COVID-19

Abstract: Background Pathogenic genetic testing for coronavirus disease 2019 (COVID-19) can detect viruses with high sensitivity; however, there are several challenges. In the prevention, testing, and treatment of COVID-19, more effective, safer, and convenient methods are desired. We evaluated the possibility of monocyte distribution width (MDW) as an infection biomarker in COVID-19 testing. Methods The efficacy of MDW as a screening test for COVID-19 was r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…MDW, which has been used as a novel biomarker for the detection of sepsis, 70 has been reported in several recent studies on COVID-19. 71,72 In our pooled results, MDW showed the superior discriminatory ability in identifying SARS-CoV-2 infection. Shahri et al identified significant differences in the function and morphology of monocytes between COVID-19 patients and healthy individuals, 73 supporting the view that MDW can help to identify COVID-19 patients.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…MDW, which has been used as a novel biomarker for the detection of sepsis, 70 has been reported in several recent studies on COVID-19. 71,72 In our pooled results, MDW showed the superior discriminatory ability in identifying SARS-CoV-2 infection. Shahri et al identified significant differences in the function and morphology of monocytes between COVID-19 patients and healthy individuals, 73 supporting the view that MDW can help to identify COVID-19 patients.…”
Section: Discussionmentioning
confidence: 62%
“…MDW, which has been used as a novel biomarker for the detection of sepsis, 70 has been reported in several recent studies on COVID-19. 71,72 In our pooled results, MDW showed the superior discriminatory ability in identifying SARS-CoV-2 infection. 75 suggesting that MDW may be a useful tool for predicting a higher risk of adverse outcomes in COVID-19.…”
Section: Discussionmentioning
confidence: 67%